2022
DOI: 10.1093/ofid/ofac065
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Syndromes Associated With Daptomycin Use: Re-exposure Hypersensitivity Pneumonitis and Prior Peripheral Eosinophilia

Abstract: Background Daptomycin pulmonary eosinophilia (DPE) has been well described in case reports and reporting from the Food and Drug Administration. We report 3 eosinophilic syndromes associated with daptomycin use. Methods This is a retrospective review of all patients who received daptomycin (inpatient or outpatient) from 2010 to 2020 at the Veterans Affairs Portland Healthcare System. Patients who developed DPE while receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…8 Furthermore, a retrospective review of 330 patients found that 81.5% of patients with DIEP demonstrated 5% or greater peripheral eosinophilia, suggesting the utility of peripheral eosinophilia in the diagnosis of DIEP. 9 The case patient had 5.8% peripheral eosinophilia, supporting the final diagnosis of DIEP.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…8 Furthermore, a retrospective review of 330 patients found that 81.5% of patients with DIEP demonstrated 5% or greater peripheral eosinophilia, suggesting the utility of peripheral eosinophilia in the diagnosis of DIEP. 9 The case patient had 5.8% peripheral eosinophilia, supporting the final diagnosis of DIEP.…”
Section: Discussionmentioning
confidence: 57%
“…Although 25% or greater eosinophils on BAL is one of the criteria for diagnosing DIEP, one literature review found that fewer than 50% of patients reviewed had greater than 25% eosinophils on BAL 8. Furthermore, a retrospective review of 330 patients found that 81.5% of patients with DIEP demonstrated 5% or greater peripheral eosinophilia, suggesting the utility of peripheral eosinophilia in the diagnosis of DIEP 9. The case patient had 5.8% peripheral eosinophilia, supporting the final diagnosis of DIEP.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood eosinophilia was defined as an eosinophil count > 1% of the total white blood cell count. Daptomycin-related peripheral blood eosinophilia was defined as an eosinophil count ≥ 5% of the total white blood cell count on two consecutive blood draws [ 10 ]. Daptomycin-induced eosinophilic pneumonitis was categorized as definite, probable, or unlikely, using criteria previously defined in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…In summary, we present and review contemporary studies of SAB across a range of topics not limited to epidemiology, clinical features, multiple positive blood cultures, antibiotic choice and duration. SAB is complex and there are many important aspects that we were not able to explore further at this time including a study with eosinophilia with daptomycin [40], use of oral stepdown therapy with clindamycin [41], improvement of diagnosis using fluorodeoxyglucose positron emission tomography/ computed tomography (FDG-PET/CT) [42,43], source control such as with removal of cardiac implantable electronic devices associated with decreased mortality [44], the importance of serial negative blood cultures [45 & ], and the significance of Staphylococcus aureus bacteriuria in patients with SAB [46 & ]. In addition, optimized use of clinical scoring systems to stratify patients for therapy or best utilize echocardiography resources is a major area of investigation that could merit its own review [47][48][49][50][51][52][53][54].…”
Section: Closing Remarksmentioning
confidence: 99%